2022
DOI: 10.1021/acs.est.1c08282
|View full text |Cite
|
Sign up to set email alerts
|

Iron Nitride Nanoparticles for Enhanced Reductive Dechlorination of Trichloroethylene

Abstract: Nitriding has been used for decades to improve the corrosion resistance of iron and steel materials. Moreover, iron nitrides (Fe x N) have been shown to give an outstanding catalytic performance in a wide range of applications. We demonstrate that nitriding also substantially enhances the reactivity of zerovalent iron nanoparticles (nZVI) used for groundwater remediation, alongside reducing particle corrosion. Two different types of Fe x N nanoparticles were synthesized by passing gaseous NH 3 /N 2 mixtures ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 81 publications
(190 reference statements)
2
44
0
Order By: Relevance
“…(3) The synthetic method for these oxide/nitrides has been well-documented in the literature, and TiN, CoN, VN, and Mo 2 N are also the most stable and common phases among their nitrides. 23,31,32 (4) The TiO 2 , Co 3 O 4 , V 2 O 5 , and MoO 3 showed different morphologies�nanoparticles, nanosheet, nanoflower, and nanobelt�which enables us to study the morphology effect (see infra), and (5) these TMNs that have been reported are rich in electrons, which is the core reason for our selection. 22 As the d-band center theory is a highly intuitive method to explore how electronic structures influence catalytic activity, we predicted the modulated electronic states of Pd sites on different TMNs and TMOs as well as their d-band centers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…(3) The synthetic method for these oxide/nitrides has been well-documented in the literature, and TiN, CoN, VN, and Mo 2 N are also the most stable and common phases among their nitrides. 23,31,32 (4) The TiO 2 , Co 3 O 4 , V 2 O 5 , and MoO 3 showed different morphologies�nanoparticles, nanosheet, nanoflower, and nanobelt�which enables us to study the morphology effect (see infra), and (5) these TMNs that have been reported are rich in electrons, which is the core reason for our selection. 22 As the d-band center theory is a highly intuitive method to explore how electronic structures influence catalytic activity, we predicted the modulated electronic states of Pd sites on different TMNs and TMOs as well as their d-band centers.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Metal nitrides were synthesized via the nitridation of their corresponding oxides in a NH 3 atmosphere . Of note is that to testify the generality of proposed method, here, we also selected a commercially available metal oxide, P 25 TiO 2 NPs, as the processor to synthesize Ti 2 N. Specifically, 1.0 g of P 25 TiO 2 NPs, MoO 3 nanobelts, or Co 3 O 4 nanosheets was loaded into a quartz boat and placed in a tubular furnace.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, nano ZVI has become a promising strategy for the treatment of CVOCs from polluted soil and groundwater (Mdlovu et al, 2019;Galdames et al, 2020). Iron nanoparticles were found to augment the reduction reaction of trichloroethylene dechlorination (Brumovsky et al, 2022). The nanometer size enhances mobility via the porous media, and the low toxicity of nano-ZVI augments the remediation processes while preserving soil properties, allowing subsequent application of other processes, such as biological remediation, unaffected (Lefevre et al, 2016).…”
Section: Degradation By Metallic Nanocatalystsmentioning
confidence: 99%